2014
DOI: 10.1007/s10552-014-0469-0
|View full text |Cite
|
Sign up to set email alerts
|

Intake of fruit and vegetables and risk of bladder cancer: a dose–response meta-analysis of observational studies

Abstract: This meta-analysis supports the hypothesis that intakes of fruit and vegetables may reduce the risk of bladder cancer. Future well-designed studies are required to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…The MA by Yao et al [19] was selected as the most comprehensive publication for overall fruit and vegetable intake and reported significant protective effect on bladder cancer (RR 0.81; 95 % CI 0.67–0.99; I 2  = 58.4 %; n = 10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The MA by Yao et al [19] was selected as the most comprehensive publication for overall fruit and vegetable intake and reported significant protective effect on bladder cancer (RR 0.81; 95 % CI 0.67–0.99; I 2  = 58.4 %; n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…MA by Yao et al [19] was selected as most comprehensive for consumption of overall fruit and the MA by Liang et al [20] for intake of citrus fruit (e.g. oranges, lemons, limes, and grapefruits;).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A metaanalysis published in 2014 confirmed the role of fruits and vegetables in the reduction of bladder cancer risk [39]; the findings of Park et al, however, suggest that their intake may only lower cancer incidence in women [40]. A metaanalysis performed by Xu et al only confirmed the beneficial effects of green leafy vegetables [38].…”
Section: Fruits and Vegetablesmentioning
confidence: 99%